Pendekatan Pembelajaran: Penerapan Riset Sebagai Salah Satu Bentuk Pembelajaran Abad 21 Pada MTsN 3 Banyuwangi - Rofiah, Rofiah (Inovasi: Jurnal Diklat Keagamaan, 2024)
Research is an active, systematic and diligent investigation with the aim of finding, interpreting and revising facts, whom research there is a series of processes ranging from finding research problems or ideas to publishing research results. Learning in the 21st century means learning to interprets 21st century skills including critical, creative, communicative and collaborative (4 C). MTsN 3 Banyuwangi has been designated as a research Madrasah since 2020. The purpose of this research is to analyze research implementation and research as a form of 21st century learning at Madrasah Tsanawiyah Negeri 3 Banyuwangi. This research is a qualitative research. This research is conducted on students in grade 7,8, and 9 of MTsN 3 Banyuwangi and was carrioud for 8 months starting from March to October 2023. The participants in this research were 8 research learning teachers and 23 students registered in the research club. The data in this research was taken through observation and semi-structured interviews. The result of this research shows that research learning at MTsN 3 Banyuwangi has not been optimal, due to several reasons especially the research supervisor team which always changes with in every new school academic year. The solutions implemented by Madrasah to overcome this problem include selecting of a new research team that is considered more competent, research curriculum making, sorting of student who are members of research clubs according to their “passion” in their respective fields, continuous and targeted guidance, planning for research process collaboration with other related agencies and universities. Key Words: Research Implementation, 21st century learning, MTsN 3 Banyuwangi